Quantum and Closed-Orbit Theory Calculations for the Photodetachment cross Sections of $H^-$ near Two Perpendicular Elastic Planes (Journal of Atomic and Molecular Sciences, 2016)
The photodetachment cross section of $H^-$ near two perpendicular elasticplanes is investigated in this paper. Both the traditional quantum approach and closedorbit theory are applied to explicitly derive the formulas of the cross section for differentlaser polarization direction. We first compared the quantum formulas with closedorbit theory formulas, and then found that the quantum results are shown to be ingood agreement with the semiclassical results. Furthermore, we also found that thecross section depends strongly on the direction of the laser polarization. When the polarizationis parallel to the closed orbit, the corresponding oscillation in the cross sectionis very obvious. However, When the polarization is perpendicular to the closedorbit, the corresponding oscillation is too small for closed-orbit theory formula to describe.